Tensile behavior of lignocellulosic fiber reinforced polymer composites: Part II buriti petiole/polyester - Portela,T.G.R. (2010)
The current interest for natural fibers as an environmentally correct composite reinforcement has motivated the investigation of new possibilities. For instance, the fibers extracted from the petiole of the buriti palm tree were recently found to have adequate mechanical properties to reinforce polymer composites. Therefore, the present work evaluates the tensile properties of polyester composites incorporated with thinner buriti petiole fibers for improved mechanical performance. Composites with up to 40% in volume of buriti petiole fibers embedded in orthophtalic polyester matrix were post-cured and then ruptured in tension. Fracture surfaces were analyzed by scanning electron microscopy. A marked increase in the tensile strength was found with the amount of buriti fibers. The fracture analysis revealed aspects of the bonding condition at the fiber/matrix interface, which could be associated with the composite performance.